2022
DOI: 10.3390/nu14061135
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Carbohydrate versus Fat Restriction on Lipid Profiles in Highly Trained, Recreational Distance Runners: A Randomized, Cross-Over Trial

Abstract: A growing number of endurance athletes have considered switching from a traditional high-carbohydrate/low-fat (HCLF) to a low-carbohydrate/high-fat (LCHF) eating pattern for health and performance reasons. However, few studies have examined how LCHF diets affect blood lipid profiles in highly-trained runners. In a randomized and counterbalanced, cross-over design, athletes (n = 7 men; VO2max: 61.9 ± 6.1 mL/kg/min) completed six weeks of two, ad libitum, LCHF (6/69/25% en carbohydrate/fat/protein) and HCLF (57/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 50 publications
(78 reference statements)
3
6
0
Order By: Relevance
“…In accordance with our findings, prior studies have reported chronic hypercholesterolemia following a KD in trained athletes [ 9 , 10 , 22 , 23 , 25 ], with some (similar to our study) observing increases in TC after 14-d [ 23 ], highlighting the rapid nature of these alterations following this extreme dietary shift. Under normal circumstances, aerobic exercise at higher training intensities alters blood lipids by directly increasing HDL-C and decreasing LDL-C [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our findings, prior studies have reported chronic hypercholesterolemia following a KD in trained athletes [ 9 , 10 , 22 , 23 , 25 ], with some (similar to our study) observing increases in TC after 14-d [ 23 ], highlighting the rapid nature of these alterations following this extreme dietary shift. Under normal circumstances, aerobic exercise at higher training intensities alters blood lipids by directly increasing HDL-C and decreasing LDL-C [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite energy intake and training load being similar between LCHF and HCLF diets, weight-loss and diet did not modulate triglycerides, insulin/HbA 1c , and inflammation (hsCRP). Based on prior evidence ( 73 , 76 ) the LCHF diet was projected to lower cardiometabolic markers beyond a HCLF diet, even in the absence of weight-loss ( 77 ); however, we did not observe these results with our between-diet isocaloric feeding design. Additionally, it is important to acknowledge that HbA 1c is a 2–3-month biomarker that we quantified to predict directional trends rather than significant changes over four weeks.…”
Section: Discussionmentioning
confidence: 68%
“…Although the overall LDL-C condition effect was significant ( p = 0.03), the LCHF diet did not increase LDL-C concentrations beyond HCLF after four-weeks (155 vs. 137 mg/dL; 18% p = 0.30), implying that post-diet hypercholesterolemia effects were predominantly determined by changes in HDL-C fraction. We anticipated based on our prior work ( 73 ) and others ( 65 , 74 , 75 ) that competitive runners would experience significant blood lipid changes within weeks after starting a LCHF designed to induce nutritional ketosis (≥ 0.5 mM R -βHB). The significant main effects in this study were directly attributable to the between-diet differences in dietary fat and fat composition, however, the fact that more than half of participants had borderline elevated total cholesterol, LDL-C, and HDL-C at baseline was somewhat unexpected.…”
Section: Discussionmentioning
confidence: 99%
“…These diets have been recommended as a treatment for patients with specific medical conditions, such as rare metabolic diseases or epilepsy, where hyperlipidemia is a well-known side effect of the ketogenic diet [ 51 , 52 ]. The ketogenic diet is gaining increasing scientific attention in the field of sports medicine, where multiple feeding trials have been conducted in healthy athletes that consistently show increases in LDL-C levels [ 53 , 54 , 55 , 56 , 57 ]. However, individual responses are variable, and LDL-C levels do not reach the levels consistent with homozygous FH, as observed in the extreme cases we presented.…”
Section: Mechanism Of Dietary Induced Hypercholesterolemiamentioning
confidence: 99%